UNIT 3.3 Culture and Isolation of Brain Tumor Initiating Cells. (3rd August 2015) - Vora, Parvez; Venugopal, Chitra; McFarlane, Nicole; Singh, Sheila K.
Abstract : Brain tumors are typically composed of heterogenous cells that exhibit distinct phenotypic characteristics and proliferative potentials. Only a relatively small fraction of cells in the tumor with stem cell properties, termed brain tumor initiating cells (BTICs), possess an ability to differentiate along multiple lineages, self‐renew, and initiate tumors in vivo. This unit describes protocols for the culture and isolation BTICs. We applied culture conditions and assays originally used for normal neural stem cells (NSCs) in vitro to a variety of brain tumors. Using fluorescence‐activated cell sorting for the neural precursor cell surface marker CD133/CD15, BTICs can be isolated and studied prospectively. Isolation of BTICs from GBM bulk tumor will enable examination of dissimilar morphologies, self‐renewal capacities, tumorigenicity, and therapeutic sensitivities. As cancer is also considered a disease of unregulated self‐renewal and differentiation, an understanding of BTICs is fundamental to understanding tumor growth. Ultimately, it will lead to novel drug discovery approaches that strategically target the functionally relevant BTIC population. © 2015 by John Wiley & Sons, Inc.